New data on soluble ACE2 in patients with atrial fibrillation reveal potential value for treatment of patients with COVID-19 and cardiovascular disease. (29th October 2020) - Sama, Iziah E; Voors, Adriaan A; van Veldhuisen, Dirk J
Abstract: